Exploring Trends, Themes and Advanced Research in Business Incubation and Entrepreneurship: Bibliometrics 2015-2024 - Farliana, Nina; Feriady, Muhammad; Ikhsananto, Aan (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This article aims to conduct a bibliometric study with structural and relational approaches among the extracted documents and investigate the relationship between business incubation and entrepreneurship to provide a comprehensive overview of the field. A total of 968 articles from the Scopus database were analyzed using bibliometric science mapping and performance techniques with the help of VOSviewer software. The findings of this study highlight the annual publication trends, most cited articles, most productive authors, and most influential countries and journals. Intellectual structures were built to identify research themes and trends through co-occurrence analysis and bibliographic merging. The results of this study emphasize the importance of technology transfer, mentoring programs, entrepreneurship education, and focusing on innovation and creativity through universities and academia. The originality of this study confirms that business incubation is a growing academic field related to startups, venture formation, and entrepreneurial ecosystems, making it a discipline with great potential.